Theoretical analysis of the problem of laziness and workaholism as different types of personality attitude to labor - V. Karavaeva (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article analyzes the basic theoretical concepts of the phenomenon of workaholism and laziness in the context of attitude of the personality to labor. It also provides an analysis of the main theoretical concepts of a phenomenon of workaholism. First of all, in it features attitude of the modern person to their working activity and career, and as the reasons of interest to this problem are noted today. This article presents the detailed definition of the problem of workaholism and laziness as the main types of attitude of the personality to work. The paper considers the main approaches to these problems as domestic authors and foreign authors. The theoretical analysis of these approaches is carried out and their certain general tendency is revealed. In the article revealed that these overall trends are based on a rather one-sided examining the problem of workaholism as foreign scientists and the majority of the domestic. Moreover, the advantages and shortcomings of these theories are marked out. Indicate different approaches to the problem of the attitude to laziness. Study of the problem of laziness is offered on the basis of value-semantic and motivational personality system. The article also points to a common basis and reason of laziness and addictive workaholism. The author offers its own approach to the problem of workaholism and laziness, proceeding from broader understanding of these phenomenons. Is offered to consider the phenomenon of workaholism and laziness from different angles, identify clear criteria of these phenomena and differentiate their different types.